2022
DOI: 10.2176/jns-nmc.2021-0426
|View full text |Cite
|
Sign up to set email alerts
|

Primary Dural Mucosa-associated Lymphoid Tissue Lymphoma Mimicking Falx Meningioma: A Case Report

Abstract: An 85-year-old woman presented with ataxia and deterioration of cognitive functions. She had no history of autoimmune diseases or viral infections. Magnetic resonance imaging showed a solitary mass lesion at the cerebral falx on contrast-enhanced T1-weighted imaging. Gross total resection of the lesion involving the dura mater was performed by bifrontal craniotomy. Histological examination showed diffuse infiltration of small lymphocytes and plasma cells. There was also some proliferation of large lymphocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…[ 3 ] EMZMBCLs are highly radiosensitive, and surgery followed by focal low-dose radiotherapy has shown good outcomes. [ 10 ] In the present case, whole-brain (21 Gy in 14 fractions) and intensity-modulated radiation therapy (9 Gy in 6 fractions) were administered as adjuvant therapies, resulting in favorable tumor control with no recurrence of EMZMBCL. Although chemotherapy may expose patients to various risks, it may be necessary in cases of secondary or recurrent EMZMBCL.…”
Section: Discussionmentioning
confidence: 98%
“…[ 3 ] EMZMBCLs are highly radiosensitive, and surgery followed by focal low-dose radiotherapy has shown good outcomes. [ 10 ] In the present case, whole-brain (21 Gy in 14 fractions) and intensity-modulated radiation therapy (9 Gy in 6 fractions) were administered as adjuvant therapies, resulting in favorable tumor control with no recurrence of EMZMBCL. Although chemotherapy may expose patients to various risks, it may be necessary in cases of secondary or recurrent EMZMBCL.…”
Section: Discussionmentioning
confidence: 98%
“…It is characterized as a slowly growing dural mass that is not infiltrative or has systemic involvement. 4 Although the pathogenesis of dura-origin MALT lymphoma is not known, the hypothesis has been suggested that monoclonal expansion resulting from subclinical inflammation in the dura could originate from the accumulation of lymphocytes in the region. As there is a predominance of female population, it has also been suggested that there could be a hormonal role in the pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized as a slowly growing dural mass that is not infiltrative or has systemic involvement. 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An especially rare location is the central nervous system (CNS) and the dura mater. Little more than 100 cases of dural MALT lymphoma have been reported in the past [2,13,16]. Generally, most MALT lymphoma cases occur in adults, with a median patient age in the seventh decade of life.…”
Section: Introductionmentioning
confidence: 99%